GAP ANALYSIS OF PRO-ENVIRONMENTAL BEHAVIOR AMONG SBM ITB STUDENTS - Honasan, Elias Yahya; Iskandar, Budi Permadi (Journal of Business and Management, 2018)
Abstract. Environmental problems in Indonesia need to be highlighed for the community. There are a lot of people who do not care about the environment and it becomes a question. This study aims to find out the reason and the gap what makes people do not care maintaining and taking care of the environment. The data collected through interview  and  using  an  online  questionnaire. Interviews  are  conducted in  an  informal  way  by  discussing environmental topics. Questionnaires were made to inquire the expectations and realities that exist about pro- environment behavior. Interview data was processed by coding method and questionnaire data was processed by different test method using paired T-test. The data are gathered from SBM ITB students class of 2018, 2019, and 2020 in period of June 2018 until July 2018 in SBM ITB. Individuality, Responsibility, and Practicality are the factors that highlighted in this study. The results shows that people are hampered to perform environmenta l conservation activities because there is a large gap on the factor of practicality.Keywords: Gap, Pro-Environment, Different Test, Individuality, Responsibility, Practicality.